Inverted-relief cavity used in VCSELs to suppress higher-order transverse modes - Sarzała, Robert; Nakwaski, Włodzimierz (Photonics Letters of Poland, 2014)
One of the most acute VCSEL disadvantages is an excitation of higher-order transverse modes in devices emitting more intense radiation. The paper presents results of simulation of VCSEL performance with the aid of the inverted-relief cavity used to suppress those modes. This suppression method is very efficient and relatively simple from technological point of view, so it is worth to be recommended. Full Text: PDF References C. Jung, R. Jäger, M. Grabherr, P. Schnitzer, R. Michalzik, B. Weigl, S. Müller, K.J. Ebeling, "4.8 mW singlemode oxide confined top-surface emitting vertical-cavity laser diodes", Electron. Lett. 33, 1790 (1997). CrossRef W. Nakwaski, "VCSEL structures used to suppress higher-order transverse modes", Opto-Electr. Rev. 19, 119 (2011). CrossRef R. Sarzała, T. Czyszanowski, M. Wasiak, M. Dems, Ł. Piskorski, W. Nakwaski, K. Panajotov, "Numerical Self-Consistent Analysis of VCSELs", Adv. in Opt. Techn. (2012). CrossRef H. Martinsson, J.A. Vukušič, A. Larsson, "Single-mode power dependence on surface relief size for mode-stabilized oxide-confined vertical-cavity surface-emitting lasers", IEEE Photon. Technol. Lett. 12, 1129 (2000). CrossRef H.J. Unold, S.W.Z. Mahmoud, R. Jäger, M. Grabherr, R. Michalzik, K.J. Ebeling, "Large-area single-mode VCSELs and the self-aligned surface relief", IEEE J. Sel. Top. Quantum Electron. 7, 386 (2001). CrossRef D. Supper, J. Pfeiffer, M. Ilzhöfer, Ch. Giuliani, Ch. Degen, A.P. Lima, A. Ramakrishnan, G. Ebbinghaus, G. Steinle, "Long-wavelength VCSEL with integrated relief for control of singlemode emission", Opt. Comm. 267, 447 (2006). CrossRef